Physically-Deposited Hole Transporters in Perovskite PV - Akalin, Salih Alper (2024)
This study was financially supported by the Dokuz Eylul University, the Scientific Research Projects Coordinatorship with the project code 2019.KB.MLT.004. The authors are indebted to the infrastructural support from Dokuz Eylül University, the Center for Production and Applications of Electronic Materials (EMUM), Department of Metallurgical and Materials Engineering, Yıldız Technical University Department of Physics, and Universidade Nova de Lisboa, Centro de Investigação em Materiais (CENIMAT) where research was carried out. S.A.A. acknowledges funding for a post‐doc scholarship from TUBİTAK (The Scientific and Technological Research Council of Türkiye, 2219) through grant 1059B192200308. The study was also partially supported by FCT (Fundação para a Ciência e Tecnologia, project M‐ECO2 (Industrial cluster for advanced biofuel production, ref. C644930471‐00000041) co‐financed by PRR − Recovery and Resilience Plan of the European Union (Next Generation EU). Publisher Copyright: © 2024 The Authors. Advanced Materials Technologies published by Wiley-VCH GmbH.